Daya Simpan Gula Siwalan Kristal Ditinjau Dari Jenis Pengemas Dan Kondisi Pengemasan - Rahayuningsih, Tri; Noerhartati, Endang; Rejeki, Fungki Sri; W, Endang Retno; Puspitasari, Diana (UPN VETERAN JAWA TIMUR, 2009)
This research aimed to defined a proper packaging and a Â way to pack for âgulaÂ siwalan kristalâ storage-life. This research used random block design which wasÂ containing two factors treatment with three (3) times repeating. First factor was theÂ kind of packaging (P1 = Polyethylene, P2 = Polypropylene). Second factor was aÂ way to pack (V1 = packing without vacuum, V2 = with vacuum). It will be analysedÂ every 5 weeks. The parameters would be analysed were water contain and sumÂ micro-organism as parameter, also hedonic test. Â Â The result showed that âgula siwalan kristalâ had a lower water contain when Â it packed by vacuum. Â Polyethylene and vacuum (P1V2) could press the amount ofÂ micro-organism. Based on hedonic test showed that a kind of packaging and a way toÂ pack did not effect to the colour of Â âgula siwalan kristalâ but did to performance of itÂ for 5, 10 and 15 weeks storages.Key words: âgula siwalan kristalâ, packaging, polyethylene, polypropylene andÂ vacuum